Mapping the fragmentation of the international forest regime complex: institutional elements, conflicts and synergies - Rodríguez Fernández Blanco, Carmen (2019)
In the field of global environmental governance, a plethora of international regimes have emerged over the past decades. In some issue areas, multiple regimes aim to govern the issue, sometimes reinforcing, oftentimes conflicting with each other. Consequently, international regime complexes are an empirical phenomenon, which are inherently characterized by specific degrees of fragmentation. For any given issue area, one of the key questions is whether the institutional fragmentation encountered in such regime complexes is synergistic or conflictive in nature. Scrutinizing this question poses methodological challenges of how to delineate a regime complex and how to assess its fragmentation. Drawing on the highly fragmented case of the international forest regime complex, this paper aims to map its institutional fragmentation and to analyse the degrees to which it is conflictive or synergistic. For this we conceptualize the notion of institutional elements and develop a novel method for mapping regime complexes based on their core institutional elements. We then employ tools from the sub-discipline of policy analysis on the complex’s institutional elements for analysing in detail, which of the elements are mutually synergistic and conflictive with other elements of the regime complex. Our results indicate that synergistic relations mostly exist among rather vague elements, often built around sustainability as a core principle. On the contrary, conflictive relations prevail as soon as the elements are designed in more concrete and substantial ways. We conclude that the forest regime complex displays only degree of seemingly synergistic fragmentation through a number of non-decisions and the use of “sustainability” as an empty formula. De facto, conflictive fragmentation prevails among elements of concrete subject matter. This raises questions on whether vast parts of regime complexes merely serve symbolic functions, while conflicts on substance are being camouflaged.